Optimal clone identifier based on dynamic rules and process algebra - Cantão, Mauricio E.; Araújo, Luciano V.; Lemos, Eliana G. M. [UNESP]; Ferreira, João E. (My University, 2009)
The rule creation to clone selection in different projects is a hard task to perform by using traditional implementations to control all the processes of the system. The use of an algebraic language is an alternative approach to manage all of system flow in a flexible way. In order to increase the power of versatility and consistency in defining the rules for optimal clone selection, this paper presents the software OCI 2 in which uses process algebra in the flow behavior of the system. OCI 2, controlled by an algebraic approach was applied in the rules elaboration for clone selection containing unique genes in the partial genome of the bacterium Bradyrhizobium elkanii Semia 587 and in the whole genome of the bacterium Xanthomonas axonopodis pv. citri. Copyright© (2009) by the International Society for Research in Science and Technology.
Keywords: Dna microarray; Npdl; Optimal clones; Process algebra; Scientific workflow; DNA micro-array; Process algebras; Scientific workflows; Algebra; Bacteria; Bioinformatics; Cloning; Genes; Optimization; Process control